Evaluating the Effectiveness of the Ummi Method in Memorizing Juz Amma for Early Chilhood Learners - Anshary, Chaliza; Suryana, Dadan; Mahyuddin, Nenny (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Research on Al-Quran teaching methods applied in schools is still very limited. Teachers play an integral role in helping young children understand and learn Arabic letters. This is very important so that children acquire reading skills and become familiar with them from an early age. So that it impacts their worship experience when they grow up. This study's criteria for memorizing Al-Quran verses (Juz Amma) include ease of pronunciation, makharijul letters and correct recitation rules. It is important to introduce short verses as basic capital in memorizing the Al-Quran. This research interviewed 2 kindergarten teachers, the principal, and two guardians of Al Azhar Rantauprapat Kindergarten students in Labuhanbatu Regency, North Sumatra Province. The focus of this research is on the process of memorizing the Al-Quran using the Ummi method. The Ummi method is a practical method for reading the Al-Quran by Tajwid rules. Muslim scholars created this method to make it easier to study the Koran. Research findings reveal that the ummi method really helps children memorize the Al-Quran/Juz Amma with the help of trained teachers (Hafiz and Hafizah).